Contribution of Mathematical Anxiety, Learning Motivation and Self-Confidence to Student’s Mathematical Problem Solving - Irhamna Irhamna; Zul Amry; Hermawan Syahputra (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The objectives of this study are to: (1) Analyze whether there is a contribution of mathematics anxiety, learning motivation and self-confidence to the ability to solve mathematical problems simultaneously, (2) Analyze whether there is a contribution of mathematics anxiety, learning motivation and self-confidence to the partial mathematical problem solving ability, (3) To analyze how big the contribution of mathematics anxiety, learning motivation and self-confidence to mathematical problem solving abilities simultaneously, (4) Analyze how much the contribution of mathematics anxiety, learning motivation and self-confidence to the partial mathematical problem solving abilit, (2) math anxiety questionnaire, (3) learning motivation questionnaire, (4) self-confidence questionnaire. Data analysis was performed by multiple linear regression analysis. The results showed: (1) There is a contribution to mathematics anxiety, learning motivation, and self-confidence to the ability to solve mathematical problems simultaneously, (2) There is a contribution to mathematics anxiety, learning motivation, and self-confidence to the ability to solve mathematical problems partially, (3) Mathematical anxiety, learning motivation and self-confidence contributed 26% to the ability to solve mathematical problems simultaneously, (4) Mathematical anxiety contributed 8.5% to mathematical problem solving abilities, learning motivation contributed 15.8% to mathematical problem solving abilities and self-confidence contributed 16.7% to mathematical problem solving abilities.